ANALYSIS OF THE STRUCTURE AND WORKING PARTS OF SAW GINNING MACHINES - Sh.T. Tursunov; M.M. Akramov; R.Y. Ruziyev (Modern American Journals, 2025)
This paper reviews the structure and function of saw ginning machines and fiber cleaners, focusing on models like 4DP-130 and 8DP-90. It presents technical improvements that enhance fiber quality and ginning efficiency.
Keywords: Saw ginning machine, cotton fiber, seed cotton processing, lint, fiber cleaning, gin saw cylinder, grate (kolosnik), collet-type grid, air chamber, trash conveyor, fiber cleaner.